ANALYSIS OF FACTORS TRIGGERING CONSUMPTIVE BEHAVIOR: A STUDY OF INSTITUT BISNIS NUSANTARA STUDENTS - Sandra, Clarisa Sonia; Yurindera, Novan (Acitya Wisesa: Journal of Multidisciplinary Research, 2025)
This study aims to examine the influence of Flash Sale Programs (Sales Promotion), Shopping Lifestyle, and Content Marketing on the Consumptive Behavior of Institut Bisnis Nusantara students on the Shopee e-commerce platform. The population of this study consists of all Institut Bisnis Nusantara students who are aware of the Flash Sale program on Shopee, with a sample of 100 respondents. Data collection was conducted using a questionnaire method distributed through Google Forms. Data processing utilized the SmartPLS application through stages of outer model analysis, inner model analysis, and hypothesis testing. The research findings indicate that Flash Sale Programs or Sales Promotion and Content Marketing do not influence the Consumptive Behavior of Institut Bisnis Nusantara students on the Shopee e-commerce platform. Meanwhile, Shopping Lifestyle significantly influences the Consumptive Behavior of Institut Bisnis Nusantara students on the Shopee e-commerce platform. These results suggest that students are more influenced by their lifestyle patterns and shopping habits rather than promotional strategies or marketing content. The findings provide valuable insights for understanding student consumer behavior in digital marketplaces and highlight the importance of lifestyle factors in shaping purchasing decisions among young consumers.